KEPEMIMPINAN KEPALA MADRASAH (Studi Peningkatan Mutu Sumber Daya Guru di MAN 2 Kota Parepare) - Mujahidin Mujahidin (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2020)
The need of a commander concerned about its subordinate by undertaking effort of quality improvement Human Resource (SDM) their teacher pass by several things that must recommended for applied by preparation education and teacher Madrasah for example; a head Madrasah must haves leadership management that have variation, effort in quality improvement that conducted head Madrasah, shall supported full of by whole stakeholder, expected every head immediately evaluation return its leadership styles currently, and try improve Human Resource (SDM) teacher quality that the of implementation. Type of this research is the approach qualitative by using case study design, data source is head Madrasah, teacher, its data collecting technique is observation technique, interview, and documentation. Result of this research to indicate that: (1) Management of head leadership Madrasah Aliyah Negeri 2 Parepare that is head Madrasah as the education leader have duty in running the functions of management, that is planning, organization development, execution, be coordination, observation, and evaluation. (2) As for effort that conducted head Madrasah in upgrading teacher resources in MAN 2 Parepare that is give motivation to teachers, conduct training activity, seminar and workshop study, giving of profession subsidy in good time, give permit to teacher energy to continue study S2. (3) Democratic leadership styles head Madrasah pushes motivation and spirit of teacher activity at MAN 2 Parepare.